2016
DOI: 10.12988/ijcms.2016.51162
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inference from the Kumaraswamy-Weibull distribution with applications to real data

Abstract: In this article, we introduce a Bayesian analysis for the Kumaraswamy-Weibull (Kum-W) distribution. Approximate Bayes estimates are obtained under the assumptions of non-informative priors using the Gibbs sampling procedure. This procedure allows for generating samples from posterior distributions. Also, using Bayesian framework, the predictive density for a single future response, a bivariate future response, and several future responses are derived. The predictive means, standard deviations, highest predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The KumW distribution has been considered by some authors, for example, [ 22 , 23 ] discussed different types of statistical inference for constant stress accelerated life tests based on censored sampling data from the KumW distribution. [ 24 ] discussed some Bayesian analyses for the KumW distribution. [ 25 ] considered a regression model for bivariate random variables based on the bivariate KumW distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The KumW distribution has been considered by some authors, for example, [ 22 , 23 ] discussed different types of statistical inference for constant stress accelerated life tests based on censored sampling data from the KumW distribution. [ 24 ] discussed some Bayesian analyses for the KumW distribution. [ 25 ] considered a regression model for bivariate random variables based on the bivariate KumW distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Cordeiro et al (2010) showed the availability and flexibility of the estimation using the KW model by the maximum likelihood (ML) method. The Bayes estimates for the parameters of the distribution using the Gibbs sampling procedure are obtained by Mandouh (2016). Mandouh (2016) adopted a non-informative prior that gives little information about the parameters, a priori, and inexact hyperparameters.…”
Section: Introductionmentioning
confidence: 99%
“…The Bayes estimates for the parameters of the distribution using the Gibbs sampling procedure are obtained by Mandouh (2016). Mandouh (2016) adopted a non-informative prior that gives little information about the parameters, a priori, and inexact hyperparameters. The main aims of the work are: (1) To propose the simplest form for Lindley approximation of the posterior mean, (2) To examine the performances of the approximate Lindley estimators in the case of the multiparameter model such as Kumaraswamy Weibull; and (3) To show the capability and flexibility of using the KW distribution for estimation using the wellknown Bayesian methods (Huber and Train, 2001) under two loss functions.…”
Section: Introductionmentioning
confidence: 99%